(untitled) (Progressive Agriculture, 2013)
Leaf mosaic transmitted by whitefly is a devastating disease of jute. It is thought to be caused by a virus belonging to begomovirus genus under geminivirus family. To confirm the identity of the causal agent, infected and healthy leaves were studied using light microscope and by using polymerase chain reaction (PCR) technique of DNA. The inclusion bodies were observed under light microscope as large, blue-violet, prominent inclusion bodies in the nucleus of the infected leaf tissues. In molecular detection technique DNA from infected and healthy plants was extracted and analyzed by polymerase chain reaction (PCR) using degenerate primers PALIv1978/PARIc496. PCR fragment of the expected size 1.2kb for the common region (CR) in the geminivirus were obtained from infected plants. DNA collected from healthy plant did not show any band during electrophoresis. Therefore, it can be concluded that leaf mosaic of jute is cause by a virus. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16463 Progress. Agric. 22(1 & 2): 19 - 25, 2011